Perampasan Hak dan Kesejahteraan Petani oleh Tengkulak di Kabupaten Aceh Barat - Rudi Andika; Marzuki Marzuki; Rahmad Halomoan Lubis; Cut Vely Muliyana; Safrida Safrida (Universitas Teuku Umar, 2020)
Agriculture is one of the main centers as source of livelihood for the people in west aceh regency, this can be seen from the yields of farmers which are increasing every year. However, the increase in yields is inversely proportional to the welfare of the west aceh farmers, due to the influence of price manipulation by middlemen. This study aims to examine the role and supervision of the government in protecting the rights of farmers from middlemen in west Aceh district. The method used in this research is qualitative with a variety of secondary data analysis techniques and used scientific narrative review data analysis techniques. The results show that discrimination against farmer by middlemen was indeed common in west Aceh. The role of the west Aceh government in overcoming this problem is by providing education, issuing policies on program for providing business capital to farmers. Meanwhile, the supervision that the goverment faces is in the form of a minumun level of public response to policies that have been regulated by the government and a lack of trust from the peasant community in the government.